The Penguin book of outer space exploration : NASA and the incredible story of human spaceflight - Logsdon, John M., 1937-; Nye, Bill (Penguin Books, 2018)
"Using items in the NASA archive together with expert narrative guidance, this history of how Americans got to space begins with Wernher von Braun's vision for voyaging to Mars and ends with Elon Musk's contemporary plan to get there. It covers the founding of NASA, the first American astronauts in space, the moon landings, the Challenger disaster, and the Hubble Telescope repairs"--